(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This article analyzes methodologies for assessing socio-economic efficiency of local investment projects in Uzbekistan based on empirical analysis of 147 regional projects implemented during 2020-2024 with total investment of 48.7 trillion UZS.